Courting Coolness - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet provides tips for keeping a house cool during the summer such as sprinkling water on porches, closing shades and blinds, and ridding the household of exposed dark surfaces. Provides examples demonstrating how the color of a surface affects the amount of heat absorbed and suggests painting a home's exposed surfaces in light colors. Finally, describes potential wall colors for optimizing coolness in one's home. Includes small photographs throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc., formed in 1933, was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Paint materials; Linseed oil; Oilseeds; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint; Heat--Transmission; Heat--Radiation and absorption